Respuesta :
6 x³ + 4 x² - 6 x - 4 = 2 x² ( 3 x + 2 ) - 2 ( 3 x + 2 ) =
= ( 3 x + 2 ) ( 2 x² - 2 ) =
= 2 ( 3 x + 2 ) ( x² - 1 ) =
= 2 ( x + 1 ) ( x - 1 ) ( 3 x + 2 )
Answer: k = 1
= ( 3 x + 2 ) ( 2 x² - 2 ) =
= 2 ( 3 x + 2 ) ( x² - 1 ) =
= 2 ( x + 1 ) ( x - 1 ) ( 3 x + 2 )
Answer: k = 1
The value of in given factor form of polynomial is value of k=1.
The given polynomial is,
[tex]6 x^{3} + 4 x^{2} - 6 x - 4 = 2 ( x + k )(x-k) ( 3 x + 2 )[/tex]
We have to find the value of k
So
[tex]6 x^{3} + 4 x^{2} - 6 x - 4[/tex]
What is the common factor in above polynomial
2
So factor out 2 we get,
[tex]= 2 (3x^2+2x^2-3x-2)\\[/tex]
[tex]= 2 (x^2(3x+2)-(3x+2)[/tex]
[tex]=2(x^2-1)(3x-2)\\=2(x+1)(x-1)(3x-2)[/tex]
Compare above with the given factor form of polynomial we get,
k=1
Therefore we get the value of k=1
To learn more about factor of three degree polynomial visit:
https://brainly.com/question/22362896